Novel One-Pot Synthesis of Xanthones via Sequential Fluoride Ion-Promoted Fries-Type Rearrangement and Nucleophilic Aromatic Substitution - Fujimoto, Yuuki; Itakura, Ryohei; Hoshi, Hiroki; Yanai, Hikaru; Ando, Yoshio; Suzuki, Keisuke; Matsumoto, Takashi (Synlett, 2013)
A novel and efficient synthesis of xanthones is described. 2-(Trimethylsilyl)phenyl 2-fluorobenzoate derivatives undergo Fries-type rearrangement and intramolecular SNAr reaction in a one-pot sequential manner under fluoride ion-promoted mild conditions. The method provides efficient access to xanthones that have significant steric congestion around the C9 carbonyl, which are not readily available by conventional methods.
Keywords: xanthone; Fries-type rearrangement; nucleophilic aromatic substitution; fluoride ion